Pengaruh Displin Kerja dan Self Efficacy Terhadap Kinerja Pegawai Kecamatan Tambaksari Pemerintah Kota Surabaya Dengan Lingkungan Kerja Sebagai Variabel Intervening - Vira Mutiarani; Hermien Tridayanti (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine and analyze the Influence of Work Discipline and Self Efficacy on Employee Performance in Tambaksari District, Surabaya City Government with Work Environment as an Intervening Variable. The study was conducted with a survey research design on 50 employees at the Tambaksari District Agency, Surabaya City, East Java Province using data types through primary data with questionnaire distribution. The variables used are Work Discipline and Self Efficacy as independent variables, and Employee Performance as the dependent variable, Work Environment Variable as an Intervening Variable. The analysis method used is PLS-SEM with the SmartPLS 4.0 software tool. The results of the study show that Work Discipline has a positive and insignificant correlation with Employee Performance at the Tambaksari District Agency, Surabaya City Government, East Java Province. Then, Self Efficacy has a positive and insignificant correlation with employee performance at the Tambaksari District Agency, Surabaya City Government, East Java Province. This study also found that Work Discipline and Self Efficacy have a positive and insignificant correlation with Employee Performance at the Tambaksari District Agency, Surabaya City Government, East Java Province through the Work Environment.